Conjugated microporous polymer foams with excellent thermal insulation performance in a humid environment. Issue 23 (14th April 2021) - Feng, Nianyun; Wu, Shujuan; Song, Danna; Li, Yimeng; Lu, Naijia; Sun, Lei; Yu, Tie; Li, An; Deng, Weiqiao
Abstract : This work reported two monolithic conjugated microporous polymer (CMP) foams synthesized through the Sonogashira–Hagihara cross-coupling reaction without mechanical stirring. Abstract : This work reported two monolithic conjugated microporous polymer (CMP) foams synthesized through the Sonogashira–Hagihara cross-coupling reaction without mechanical stirring. The as-synthesized (CMP-ED and CMP-PT) foams exhibited superior hydrophobicity and low apparent density of 58 mg cm −3 and 63 mg cm −3 . In addition, CMP-ED displayed a low thermal conductivity of 34.04 mW m −1 K −1, which was comparable with commercial SiO2 aerogels (34.09 mW m −1 K −1 ) at 50% humidity conditions. When the environment humidity was raised from 50% to 70%, the thermal conductivity of CMP-ED and commercial SiO2 aerogels improved by 0.12% and 7%, respectively. Furthermore, XRD, FTIR, BET and TG were conducted to evaluate the bulk structure and stability of CMP-ED and CMP-PT. The results illustrated the thermal conductivity values were greatly affected by the pore structure of foams. And the strong hydrophobicity and the narrow pore structure were responsible for the good thermal insulation performance under humid conditions. Considering the low density, superhydrophobicity, excellent physicochemical stability and impervious thermal conductivity in a high humidity environment, this CMP-ED presented great potential as an insulating material in a humid environment.